2007
DOI: 10.2174/157339607782411547
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in Meconium Aspiration Syndrome: Targets for Pharmacological Modulation

Abstract: Pathophysiology of meconium aspiration syndrome (MAS) is complex and interactions between individual pathomechanisms are still not completely understood. As recently shown, inflammation plays a significant role in the pathogenesis of MAS. Activated cells release and stimulate production of a wide variety of mediators, including cytokines, enzymes, reactive species, and other biologically active substances in meconium-injured lungs. Anti-inflammatory drugs acting on different levels of inflammatory cascade may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 146 publications
(205 reference statements)
2
7
0
Order By: Relevance
“…In a piglet model of MAS, pretreatment with corticosteroids before meconium instillation decreased the pulmonary artery pressure, pulmonary vascular resistance, and right‐to‐left pulmonary shunts by preventing an increase in the post‐arterial resistance, 11,13 probably via suppressed formation of vasoconstrictor eicosanoids and increased production of vasodilator prostanoids, such as prostacyclin 16 . In newborns with severe MAS, dexamethasone treatment improved lung functions and facilitated weaning from the ventilator 14,15 . In the present study enhanced oxygenation and slightly decreased PaCO 2 were found early after dexamethasone treatment, with maximum effect within the first hour after dexamethasone administration.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In a piglet model of MAS, pretreatment with corticosteroids before meconium instillation decreased the pulmonary artery pressure, pulmonary vascular resistance, and right‐to‐left pulmonary shunts by preventing an increase in the post‐arterial resistance, 11,13 probably via suppressed formation of vasoconstrictor eicosanoids and increased production of vasodilator prostanoids, such as prostacyclin 16 . In newborns with severe MAS, dexamethasone treatment improved lung functions and facilitated weaning from the ventilator 14,15 . In the present study enhanced oxygenation and slightly decreased PaCO 2 were found early after dexamethasone treatment, with maximum effect within the first hour after dexamethasone administration.…”
Section: Discussionsupporting
confidence: 56%
“…In the present study we found no significant effect of single‐dose dexamethasone on systemic blood pressure, CVP, or right‐to‐left pulmonary shunts compared to the non‐treated meconium‐instilled group in the evaluated time intervals. Similarly, in piglets with MAS, administration of dexamethasone after meconium instillation did not influence the pulmonary artery pressure, pulmonary vascular resistance, stroke volume, MBP or heart rate, when compared to meconium‐instilled non‐treated animals 12–14 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This may potentiate the lung injury and inhibit lung surfactant production (Mokra & Mokry, 2007; 2010)…”
Section: Enzymatic Action Of Nosmentioning
confidence: 99%
“…anti-cytokine antibodies, inhibitors of complement, inhibitors of angiotensin converting enzyme, anticoagulants, inhibitors of proteolytic enzymes, calcium-channel blockers etc. that may be beneficial in MAS [5].…”
Section: Introductionmentioning
confidence: 99%